Boardroom or War Room: An Expectational Analysis of CFO – Executive Board Relationships in Adventist Local Conferences - Brown Sr., Theodore (Archives of Business Research, 2018)
The Board of Directors represents the highest level of organizational governance, and is the governing body in corporate organizations; primarily responsible for the oversite of the operations and interests of the shareholders and/or stakeholders of the business and/or entity. The basis of this quantitative paper was instigated by the thought that the perceptions of Seventh-day Adventist (SDA) Local Conference leadership consequentially impact how the relationships of Chief Financial Officer(s) (CFOs/Treasurers) and their Executive Board(s) are viewed and interact based upon perceived expectations. The corporate relationships between the Chief Financial Officer(s) (CFOs) and Executive Board(s) have continued to emerge as a result of changing societal and global expectations of what is expected from organizations from shareholders, stakeholders and governments. The 21st century inception of significant governmental regulations mainly called the Sarbanes-Oxley Act was passed to address and counteract emerging and widespread corruption in large USA businesses and organizations, extensive financial reporting fraud, institutional mis-management and material non-compliance in accounting practices. This legislative act redefined the relational expectations and practices of board governance and board member duties, Chief Executive Officer (CEO) and Chief Financial Officer (CFO) corporate and organizational accountability. The magnitude of the Sarbanes-Oxley Act has also affected the relational practices of Chief Financial Officers (CFOs/Treasurers) and Executive Board(s) in Seventh-day Adventist (SDA) conferences. Data was collected from a purposeful sample of N=399 at fifty-seven Seventh-day Adventist (SDA) Local Conferences in the North American Division territory inclusive of Bermuda, Canada and the United States of America (USA) with a 55% response rate. A Mixed-Methods sequential exploratory research design utilizing Descriptive Statistics, ANOVAs and Chi-Square Analysis was used focusing on the quantitative aspects and results of this study. Discussion and Conclusion are explored and disclosed, and the Implications of Chief Financial Officer (CFO) and Executive Board relationships on organizational governance and accountability pertaining to the overall organizational climate, effectiveness, operational efficiency are discussed.